2011
DOI: 10.1080/19475705.2010.541501
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of SWIR-based methods for quantifying active volcano radiant emissions using NASA EOS-ASTER data

Abstract: Analysis of thermally emissive volcanic features using satellite infrared remote sensing has been conducted over recent decades, primarily using shortwave and thermal infrared (SWIR; TIR) radiance data. The Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER), mounted on the Earth Observation System (EOS) Terra satellite, offers an advance on earlier instruments, having more bands covering the SWIR atmospheric window and offering a wider dynamic range. This paper compares methods used to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…In comparing the detection limits of Landsat 8's OLI SWIR bands, with those of its predecessor, Landsat ETM+, the enhanced dynamic range of the former means that temperatures of up to 747.9 K and 570.4 K can be detected without saturation in Bands 6 (1.56-1.66 µm) and 7 (2.10-2.30 µm), as compared with those for the corresponding ETM+ bands (724.5 and 552.8 K, respectively) [33]. The problem of saturation was demonstrated in [19], in which it was found that 16% of the volcanic ASTER SWIR scenes analysed displayed saturation, thereby preventing their quantitative analysis. One solution for saturation is the use of varying gain settings to extend the maximum detectable temperatures at the higher end.…”
Section: Specific Considerations For the Infrared Remote Sensing Of Vmentioning
confidence: 97%
See 4 more Smart Citations
“…In comparing the detection limits of Landsat 8's OLI SWIR bands, with those of its predecessor, Landsat ETM+, the enhanced dynamic range of the former means that temperatures of up to 747.9 K and 570.4 K can be detected without saturation in Bands 6 (1.56-1.66 µm) and 7 (2.10-2.30 µm), as compared with those for the corresponding ETM+ bands (724.5 and 552.8 K, respectively) [33]. The problem of saturation was demonstrated in [19], in which it was found that 16% of the volcanic ASTER SWIR scenes analysed displayed saturation, thereby preventing their quantitative analysis. One solution for saturation is the use of varying gain settings to extend the maximum detectable temperatures at the higher end.…”
Section: Specific Considerations For the Infrared Remote Sensing Of Vmentioning
confidence: 97%
“…Early on, the relatively fine spatial resolution of ASTER's infrared bands was shown to be useful in detecting eruption-precursory thermal anomalies at Chikurachki Volcano, Russia [58], while [19,59] demonstrated that despite its sub-optimal revisit frequency of 16 days, long-term analysis of its data could be used to characterise the behaviour of Shiveluch and Lascar volcanoes, respectively, with its SWIR and TIR bands showing utility for detecting different thermal components at each volcanic surface. Urai and Ishizuka [60] also demonstrated that within several hours of acquisition, ASTER imagery could be used to estimate the volcanic explosivity index (a scale used to quantify eruption explosiveness) of an eruption, although this relied on ASTER viewing the surface at an appropriate time.…”
Section: Historical Perspective On Sensors Used For Volcanic Observationmentioning
confidence: 99%
See 3 more Smart Citations